Gender Differences in Cooperative Environments? Evidence from the U.S. Congress - Stefano Gagliarducci; M. Daniele Paserman (Institute for the Study of Labor (IZA), 2016)
This paper uses data on bill sponsorship and cosponsorship in the U.S. House of Representatives to estimate gender differences in cooperative behavior. We employ a number of econometric methodologies to address the potential selection of female representatives into electoral districts with distinct preferences for cooperativeness, including regression discontinuity and matching. After accounting for selection, we find that among Democrats there is no significant gender gap in the number of cosponsors recruited, but women-sponsored bills tend to have fewer cosponsors from the opposite party. On the other hand, we find robust evidence that Republican women recruit more cosponsors and attract more bipartisan support on the bills that they sponsor. This is particularly true on bills that address issues more relevant for women, over which female Republicans have possibly preferences that are closer to those of Democrats. We interpret these results as evidence that cooperation is mostly driven by a commonality of interest, rather than gender per se.
Keywords: D72; D70; J16; H50; M50; 330; U.S. Congress; cooperativeness; bipartisanship; gender